From unspecific to adjusted, how the BOLD response in the rat hippocampus develops during consecutive stimulations. Issue 2 (February 2017) - Riemann, Stephanie; Helbing, Cornelia; Angenstein, Frank
To determine the possibility to deconvolve measured BOLD responses to neuronal signals, the rat perforant pathway was electrically stimulated with 10 related stimulation protocols. All stimulation protocols were composed of low-frequency pulse sequences with superimposed high-frequency pulse bursts. Because high-frequency pulse bursts trigger only one synchronized spiking of granular cells, variations of the stimulation protocol were used: (a) to keep the spiking activity similar during the presentation of different numbers of pulses, (b) to apply identical numbers of pulses to induce different amounts of spiking activity, and (c) to concurrently vary the number of applied electrical pulses and resultant spiking activity. When complex pulse sequences enter the hippocampus, an unspecific default-like BOLD response is first generated, which relates neither to the number of incoming pulses nor to the induced spiking activity. Only during subsequent stimulations does the initial unspecific response adjust to a more adequate response, which in turn either strongly related to spiking activity when low-frequency pulses were applied or depended on the incoming activity when high-frequency pulse bursts were presented. Thus, only the development of BOLD responses during repetitive stimulations can predict the underlying neuronal activity and deconvolution analysis should not be performed during an initial stimulation period.